The effect of EUSOMA certification on quality of breast cancer care. Issue 10 (October 2015) - van Dam, P.A.; Tomatis, M.; Marotti, L.; Heil, J.; Wilson, R.; Rosselli del Turco, M.; Mayr, C.; Costa, A.; Danei, M.; Denk, A.; Emons, G.; Friedrichs, K.; et al.
Abstract Aim of the study The European Society of Breast Cancer Specialists (EUSOMA) has fostered a voluntary certification process for breast units to establish minimum standards and ensure specialist multidisciplinary care. In the present study we assess the impact of EUSOMA certification for all breast units for which sufficient information was available before and after certification. Materials and methods For 22 EUSOMA certified breast units data of 30, 444 patients could be extracted from the EUSOMA database on the evolution of QI's before and after certification. Results On the average of all units, the minimum standard of care was achieved for 12/13 QI's before and after EUSOMA certification (not met for DCIS receiving just one operation). There was a significant improvement of 5 QI's after certification. The proportion of patients with invasive cancer undergoing an axillary clearance containing >9 lymph nodes (91.5% vs 89.4%, p 0.003) and patients with invasive cancer having just 1 operation (83.1% vs 80.4%, p < 0.001) dropped, but remained above the minimum standard. The targeted standard of breast care was reached for the same 4/13 QI's before and after EUSOMA certification. Conclusion Although the absolute effect of EUSOMA certification was modest it further increases standards of care and should be regarded as part of a process aiming for excellence. Dedicated units already provide a high level of care before certification, but continuous monitoring and audit remains of paramount importance as complete adherence to guidelines is difficult to achieve.